2016
DOI: 10.11604/pamj.2016.24.19.8784
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with a breast cancer in a population of Moroccan women whose age is less than 40 years: a case control study

Abstract: IntroductionBreast cancer is the most common cancer in morocco women were it occupies the first place in term of incidence and mortality. The aim of the present paper is to evaluate the risk factors associated with a breast cancer in a population of Moroccan women.MethodsA case-control study was conducted with population women whose age is less than 40 years during 2008-2010 at the National Institute of Oncology of Rabat. These women were interviewed for Epidemiological information and risk factor for breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
4
13
0
2
Order By: Relevance
“…In this study, the results showed that more respondents in the experimental group used some form of contraception, while in the 2002 study ( 12 ) there was no significant difference between the control (3.6%) and the experimental group (2.4%) and similar results are quoted by Laamiri et al ( 17 ).…”
Section: Discussionsupporting
confidence: 80%
“…In this study, the results showed that more respondents in the experimental group used some form of contraception, while in the 2002 study ( 12 ) there was no significant difference between the control (3.6%) and the experimental group (2.4%) and similar results are quoted by Laamiri et al ( 17 ).…”
Section: Discussionsupporting
confidence: 80%
“…Late menopause is associated with the risk of ductal types and lobular types of breast malignancies as well as HR+ histological type breast cancers in well-differentiated (G1) forms. 3 Menarche and menopause bring marked changes within the breast and are related to hormonal fluctuations and cellular proliferation. 16 Age at Menopause Before menopause, serum ovarian hormones circulate freely in the blood and have bioavailability to the breast, resulting in the proliferation of breast epithelial cells.…”
Section: Her2 Breast Cancermentioning
confidence: 99%
“…In univariate analysis, it was found that multiparous state decreases the risk of breast malignancies up to 74.2%. 3 Higher parity is associated with extensive breast cancer mortality among premenopausal women. A large UK cohort study found that approximately a 10% reduction in risk for each additional birth for the most common histologic types of breast malignancies is seen.…”
Section: Her2 Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations